Tidal Energy Utilization of Larantuka Strait by Dual Tidal Turbines to Increase National Energy Resilience - Soejianto, Eko; Zahra, Khansa Hanifa; Hidayah, Suci Nur (Proceeding International Conference on Science and Engineering, 2019)
Currently, renewable energy can only support 5% of national energy needs. Meanwhile, in 2035 renewable energy targeted to sustain 14% of total national energy demand. The proper way for optimizing the renewable energy is needed to actualize the target. Tidal energy as one of the potentials that are still being developed and need more attention from the government. Tidal can be used for natural energy resource since it has zero emission, produce big energy, and has no impact to weather. Larantuka Strait located in Flores island, Nusa Tenggara Timur province can produce tidal velocity up to 2.859 m/s with water density as much as 1.025 gr/cc. In utilizing this energy, we use new innovation by using dual tidal turbines which placed at the foot of Palmerah Bridge. The construction of Palmerah Bridge is built both by the government of Flores Island and Adonara Island. Dual tidal turbines are more efficient than singl e turbine by reason of tidal that has passed through the first turbine can be used again for the second turbine. The using of the generator is meant to convert kinetic energy that produced by dual tidal turbines. To convert ocean currents into electrical energy optimally, it is necessary to plan turbine designs that are in accordance with the conditions of ocean currents and the surrounding environment such as current velocity, wind influences and so on. Horizontal-axis tidal turbine (HATTs) is one of the technologies that are being developed and tested in prototype form by several companies, an efficient blade design is very important for the success of the HATTs. The amount of turbine needs, in this case, is 15 turbines with each turbine’s length is 10 meters. The turbines installed in bridge’s column along 800 meters. Estimate electricity can be generated by the turbine is 1.48 Mega Watt (MW).